The predictive factors for resorption of lumbar disc herniation - A.J. Sanginov; I.D. Isakov; V.V. Belozerov; E.A. Mushkachev; A.V. Peleganchuk (Хирургия позвоночника)
Objective. To determine the timing and to identify predictive factors of resorption of lumbar disc herniation. Material and Methods. This study is retrospective cohort and is devoted to the study of two groups of patients: Group 1 with herniated disc resorption and Group 2 with no resorption. All patients underwent MRI of the lumbar spine at the onset of initial symptoms, and the second study was conducted during the second visit. Based on the MRI results, the following parameters were assessed: the degree of intervertebral disc degeneration according to the Pfirrmann classification, the degree of facet joint degeneration according to the Grogan classification, the type of hernia, the degree of migration of the hernial fragment according to the Komori classification, Modic changes, the state of the endplates according to the Rajasekaran classification, the presence of retrolisthesis and the presence of resorption of the hernial fragment in dynamics. The Syngo.via workstation was used to measure the volume of the hernial fragment. Resorption of a disc herniation was considered to be a decrease in its volume by more than 50 % of the initial value with mandatory relief of radicular pain syndrome. The identification of resorption predictors was performed by building logistic regression models. Single-factor models were used to identify individual predictors associated with the target event. For continuous indicators, the ROC analysis identified the maximum cut-point values according to the Youden’s index. Results. Group 1 included 141 patients, and Group 2 (comparison) – 93. Statistically significant differences between groups were found in several parameters. The average age of patients was 6 years younger; the interval between MRI studies was on average 2 months longer; and the protrusive type hernias were more in Group 2 than in Group 1. Gender, body mass index, the presence of retrolisthesis and smoking habit did not differ significantly between the groups. In Group 2, there were more cases of hernia at the L5–S1 level, which is associated with a higher incidence of hernia at this level. Using logistic regression models, it was revealed that hernia volume, hernia type according to the Komori classification, body mass index and Modic changes are significant factors for hernia resorption. A hernia volume of more than 1.1 cm3, no Modic change, hernia types II and III according to Komori, and body mass index of less than 30.24 increase the chances of disc herniation resorption. Conclusion. The average time to resorption of herniated lumbar disc is 5.5 months. Factors that predict the resorption include types II and III of hernia according to the Komori classification (correspond to sequestered herniation), the absence of Modic changes, hernial fragment volume larger than 1.1 cm3, and body mass index less than 30.24.